2015
DOI: 10.1093/mnras/stv331
|View full text |Cite
|
Sign up to set email alerts
|

Studying the YMC population of M83: how long clusters remain embedded, their interaction with the ISM and implications for GC formation theories

Abstract: The study of young massive clusters can provide key information for the formation of globular clusters, as they are often considered analogues. A currently unanswered question in this field is how long these massive clusters remain embedded in their natal gas, with important implications for the formation of multiple populations that have been used to explain phenomena observed in globular clusters. We present an analysis of ages and masses of the young massive cluster population of M83. Through visual inspect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
129
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 149 publications
(155 citation statements)
references
References 44 publications
24
129
2
Order By: Relevance
“…However it is not clear whether GCs can retain gas clouds with masses of order ∼ 10 6 M for ∼ 35 Myr. Observations of young massive star clusters by Bastian, Hollyhead & Cabrera-Ziri (2014) and Hollyhead et al (2015) show that they have cleared out their natal gas within a few Myrs. If it was the case for GCs as well, then it poses a serious challenge for the scenario proposed by Krause et al (2012Krause et al ( , 2013 and would imply that either stellar winds and supernova explosions do have to expel the gas or that the gas is completely consumed into stars after a few Myr in which case the scenario suggested here would not work.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However it is not clear whether GCs can retain gas clouds with masses of order ∼ 10 6 M for ∼ 35 Myr. Observations of young massive star clusters by Bastian, Hollyhead & Cabrera-Ziri (2014) and Hollyhead et al (2015) show that they have cleared out their natal gas within a few Myrs. If it was the case for GCs as well, then it poses a serious challenge for the scenario proposed by Krause et al (2012Krause et al ( , 2013 and would imply that either stellar winds and supernova explosions do have to expel the gas or that the gas is completely consumed into stars after a few Myr in which case the scenario suggested here would not work.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Several studies have searched for gas inside young and massive clusters and up to now none have been found (e.g., Bastian & Strader 2014;Cabrera-Ziri et al 2015; see also Longmore 2015). and Hollyhead et al (2015) showed that young massive clusters expel their gas to over 200 pc in just a few Myr. It is not clear how this gas should be reaccreted to the cluster again.…”
Section: Other Considerations On Age Spreads Within Clustersmentioning
confidence: 99%
“…However, it is currently unclear how a cluster would actually do this, as young massive clusters are observed as being gas free from an early (<1−3 Myr) age and remain so (Hollyhead et al 2015;Bastian & Strader 2014). Additionally, Cabrera-Ziri et al (2015) searched for gas in three massive (>10 6 M ) clusters in the Antennae merging galaxies, with ages between 50−200 Myr, and did not detect any, which calls into doubt whether young massive clusters can host the necessary gas/dust reservoirs to form further generations of stars.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, In order to form a second generation of stars, clusters must be able to retain and/or accrete material from their surroundings (e.g., Conroy & Spergel 2011). However, clusters appear to be gas free after 2 − 3 Myr, independent of their masses from ∼ 10 4 − ∼ 10 7 M⊙ (Bastian, Hollyhead, Cabrera-Ziri 2014;Hollyhead et al 2015) and remain gas free for at least the next few hundred Myr (Bastian & Strader 2014;Cabrera-Ziri et al 2015;Longmore 2015).…”
Section: Introductionmentioning
confidence: 99%